IMPLEMENTASIBUDAYA RELIGIUS DALAMPERKEMBANGAN MORAL PESERTA DIDIK - Abdul Manan; Siti Suwaibatul Aslamiyah (Universitas Islam Lamongan, 2019)
Titled the implementation of culture religious to students moral development in MTs Tanwirul Qulub Sungelebak Karanggeneng Lamongan years lessons 2017 / 2018 aims to answer the question of how the application of religious culture in school impact the moral development in MTs. students Tanwirul Qulub Sungelebak. The implementation of tolerance attitude to the religious culture in schools it is incredibly important to be implemented.With in achieveing the goal of tolerance attitude to the religious culture will tertanamkan in the soul of a student to lose their indirect kind of way, as well as be an increase in the peace from us and the ketaqwaan students as well as strongly influenced the development of the act of moralizing school tuition. It is very relevant if we dock in the high number of a case that appear in the holy land, as as well as among students, they are promiscuous, immoral actions and ill treatment of an equality accompanied by murder case of not a few of the students cause reluctance of the doers.To express this researchers used qualitative research approach.In data collection, researchers used the interview, observation and documentation. And in data analysis, the use writers interaction which includes reduction interactive data, presentation of data and verification.The results of research obtained was first, form the implementation of culture religious in MTs. tanwirul qulub in the form of religious subjects additional namely Nahwu Shorof, Faraid, Ta’lim, Aswaja.And also be habituation of religious activities that is read the al-waqi’ah, read asmaul belong, prayer dhuha, read Tahlil together every day thursday.Second, the implementation of culture religious gives the effect on moral development school tuition.This is proven with a civility the school tuition and empathy high on teachers and others friend.